KONSEKUENSI SOSIAL PEMANFAATAN TEKNOLOGI INFORMASI - Pandu Bimantara (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
The phenomenon of the use of the internet as a learning media at the Al-Ihya (Unisa) Islamic University of Kuningan is increasingly passionate about the existence of hotspot facilities, so students can access the internet anywhere and anytime as long as they are active on the Unisa Kuningan campus. This interesting phenomenon is investigated because every new use of information and communication technology will have social consequences for the Unisa Kuningan academic community. The results of the study show that there are accessibility, frequency, and duration of internet usage by students who are quite high among students in accessing the internet. The social consequences that arise have not shown the existence of negative trends such as internet addiction and social alienation. Keywords: Internet, learning media, social consequences.